2021
DOI: 10.1111/jam.15016
|View full text |Cite
|
Sign up to set email alerts
|

Action mechanisms and biocontrol of Purpureocillium lilacinum against green mould caused by Penicillium digitatum in orange fruit

Abstract: Aims: The present study evaluated, for the first time, the inhibitory effects of the filtrate of Purpureocillium lilacinum against Penicillium digitatum. Methods and Results: No direct contact between P. lilacinum and P. digitatum was observed during the dual culture test and the inhibition zone was 6Á1 mm. The filtrate of P. lilacinum completely inhibited P. digitatum growth and spore germination at the concentration of 64%. The filtrate increased the permeability of the cell membrane and the content of MDA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 54 publications
(70 reference statements)
0
26
0
Order By: Relevance
“…Chaetomium can improve crop root quality, and because it antagonizes pathogens, the genus can be used for biological control (Ma et al, 2021 ). Purpureocillium and Metacordyceps are important in insect and nematode control (Elsherbiny et al, 2021 ). Notably, copiotrophic fungi, such as Mortierella and Chaetomium , as an important link between plants and soil, can affect the material cycle and energy conversion process in the soil environment through fierce competition for carbon sources (Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chaetomium can improve crop root quality, and because it antagonizes pathogens, the genus can be used for biological control (Ma et al, 2021 ). Purpureocillium and Metacordyceps are important in insect and nematode control (Elsherbiny et al, 2021 ). Notably, copiotrophic fungi, such as Mortierella and Chaetomium , as an important link between plants and soil, can affect the material cycle and energy conversion process in the soil environment through fierce competition for carbon sources (Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biological agents also have direct or indirect impacts on the cell membrane of fungi, affecting both membrane permeability and structure, resulting in increased leakage of critical cellular components, such as nucleic acids and proteins ( Elsherbiny et al, 2021 ). Relative conductivity, MDA content, as well as nucleic acid and soluble protein leakage are often used to determine the degree of cell membrane damage ( Dai et al, 2021 ; Elsherbiny et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biological agents also have direct or indirect impacts on the cell membrane of fungi, affecting both membrane permeability and structure, resulting in increased leakage of critical cellular components, such as nucleic acids and proteins ( Elsherbiny et al, 2021 ). Relative conductivity, MDA content, as well as nucleic acid and soluble protein leakage are often used to determine the degree of cell membrane damage ( Dai et al, 2021 ; Elsherbiny et al, 2021 ). We demonstrated that exposure to B. tequilensis YYC 155 significantly increased relative conductivity and MDA levels in the anthracnose pathogen, C. fructicola , thus increasing membrane permeability, and providing evidence of membrane structural damage ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tolerance index was calculated utilising the growth rate control on CDA, which represents a growth baseline for the strains in a stress-free condition. [48][49][50][51], Purpureocillium lilacinum was selected for further screening. In order to evaluate the difference in toxicity between the pure molecule of glyphosate (GLY) and the commercial product (RU), the species was tested in a liquid Czapeck dox medium enrichment condition without phosphorus (CDB P−) at a concentration of 1 mM both GLY and RU.…”
Section: Screening Of Fungal Strains For Their Ability To Utilise Glyphosate As Nutritional Sources Of C or Pmentioning
confidence: 99%